A CPFD simulation on the particle flow characteristics in a packed moving bed solar receiver with an added insert. (August 2021) - Nie, Fuliang; Bai, Fengwu; Wang, Zhifeng; Yang, Ronggui
Highlights: The CPFD method for dense particle flow calculation was effectively verified by experimental results and empirical correlations. The solid fraction and particle velocity profiles within a semi-annular flow channel were acquired by the CPFD method. The particle layer thickness of 5 mm was shown to be ideal to achieve a uniform distribution of axial particle velocity. Abstract: An alternative particle receiver using downward particle flow in a quartz tube with a conical hopper at the bottom has been evaluated to eliminate particle loss associated with directly irradiated solid particle solar receivers (SPSR). A computational particle fluid dynamic (CPFD) simulation is performed to investigate the particle flow characteristics in the packed moving bed quartz tube SPSR with embedded insert. Whether an insert is added in the tube or not, a consistent regular pattern is achieved for the time-varied average solid fractions at different packed heights in the tube. However, inconsistent distribution of axial particle velocity on the cross-sectional area is obtained, and the particle layer thickness affects the uniformity of the axial particle velocities. The thinner particle layer leads to a uniform distribution of axial particle velocities, and the average axial particle velocity is higher than that with a thick particle layer, which can enhance the operating safety and heat transfer of the solar receiver according to the previous investigations. In this study, the particle layer thickness of 5 mm is recommended according to the CPFD simulation. In addition, the radial movement in the semi-annular flow channel is negligible if sufficient particles are provided by the top particle dispenser. The conclusions in this cold state numerical study can provide the basis for the establishment of a further accurate thermal model for the solar receiver.